Legal framework on Islamic finance in Nigeria: a critical appraisal of Hurdles against the effective shari‘ah governance - Chiroma, Magaji; Arifin, Mahamad; Abdullah, Mohamad Asmadi; Ansari, Abdul Haseeb (2014)
Nowadays, criticisms by the antagonists of Islamic financial institutions regarding their establishment and management have been put to rest. Most countries in the world if not all, have reckoned with the successes recorded in terms of capital markets and growths of Islamic financial institutions. However, the most challenging issue in recent times is not regarding the management of the capital base of the institutions, but on how to get a feasible legal framework in modern Muslim countries that can ensure the effective Shari‘ah compliance within the sector. It is obvious that each country that operates Islamic finance in the world has its own peculiar approach to the mode of Shari‘ah governance within its Islamic financial institutions. In some countries where Islamic finance is being practiced, a distinct and full-fledged legal framework has been provided, while some countries do not have it due to the pluralistic nature of their legal systems. Other countries despite the complexity and pluralism of their legal system have still managed to have a distinct and full-fledged legal framework on Islamic finance. Nigeria is one of the modern Muslim countries that have in recent years embarked on Islamic financial activities within its financial sector. Since its involvement, a lot of challenges have been encountered; legally, politically, socially and economically. The most glaring one in recent past is regarding the issue of having an effective, independent and distinct legal framework for the Shari‘ah governance in Islamic financial institutions. The Central Bank Act, Central Bank Guidelines and the Bank and Other Financial Institution Act (BOFIA) are currently the key and major legal frameworks regulating Islamic banking (including the Shari‘ah governance) and other financial institutions in Nigeria. It is against this backdrop that this paper suggests (as per the recommendations set out herein) among other things, that the Government of Nigeria should create a better and suitable enabling environment for Islamic financial institutions to operate.